The Influence Of Financial Literacy And Perceptions Of Financial Risk On The Decision To Use Shopee Paylater Among Students At The Faculty of Economics And Business, University Of Mataram - Tyas Septianingsih; Baiq Anggun Hilendri Lestari; Rini Ridhawati (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The growth of e-commerce platforms and applications sold online is the impact of technological progress technology. Along with many feature applications, selling keeps buying online continuously increasing, and payments also increase quickly and more comfortably. The growth of internet technology is one of the forces driving e-commerce. More and more people are using the internet to shop because access is increasingly economical. Usability for online purchases, including buying and selling procedures, becomes more straightforward with "Buy Now , Pay Later." Paylater is one of the general things to research. It aims to know the influence of literacy finance and perception of finances on usage decisions on ShopeePaylater. Research Methods in Research This is quantitative associative with a level significant 5 %. Primary data used in the study originates from a questionnaire consisting of 358 respondents from the Faculty at Mataram University Economics and Business. Data analysis was carried out with the Partial Least Square (PLS) method using Smart PLS 3.0. The results of data analysis show that the variable Literacy Finance No influential significant on Usage Decisions ShopeePaylater, and Perception Risk Financial influential significant on Usage Decisions ShopeePaylater.